PENGGUNAAN MEDIA PUZZLE UNTUK MENINGKATKAN KEMAMPUAN KERJA SAMA SISWA PADA PELAJARAN IPAS DI SEKOLAH DASAR - Sarniati; Yanti Yandri Kusuma; Yusnira; Joni; Rizki Ananda (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effectiveness of puzzle media in improving students' cooperation skills on the topic of How to Get All Our Needs in science learning in grade IV of SDN 043 Batu Gajah. The background of this study is the low ability of students to cooperate in group activities, such as the absence of active participation, responsibility, and being given appreciation for friends' opinions during the discussion process. This study is a Classroom Action Research (CAR) which was carried out in two cycles, each consisting of two meetings. The research subjects consisted of 1 teacher and 20 students, with details of 8 males and 12 females. The objects in this study were puzzle media and students' cooperation skills. Data collection techniques were carried out through observation and documentation, while data analysis techniques were carried out descriptively qualitatively and quantitatively. The results of the study showed an increase in students' cooperation skills, from the initial condition of 39.25% (very poor category), increasing to 58.25% at the end of cycle I (sufficient category), and increasing again to 87% at the end of cycle II (very good category). The conclusion of this study is that puzzle media is proven to be effective in significantly improving students' cooperation skills in science learning. Keywords: Puzzle Media and Collaboration Skills